Engineering Mathematics - Meher, Ramakanta (Sciendo, 2021)
I take great pleasure in presenting this book of engineering mathematics to the students of Engineering colleges. It is prepared in accordance with the syllabus of Bachelor's degrees in Engineering and polytechnic colleges. It has been prepared by keeping the modern method of education in mind as well as the aptitude and attitude of the students to participate in various competitive examinations. In this book, the concepts are explained in a lucid manner that makes the teaching and learning process more easy and effective. Each chapter has been prepared with strenuous efforts to present the principles of the subject in the easiest manner to understand and to work out the sum of each topic of the book.Similarly, each chapter has been started with an introduction, definitions, theorems, explanation and solved examples for the better understanding of concepts.I hope that this book serves the purpose of keeping in mind the changing needs of the society to make it lively and vibrating.